Optimizing the Use of MPPT in PLTS for Hybrid Systems by Using STS as a Transfer Switch - Azmil Anil Yamin Fajrus Sodiq; Renny Rakhmawati; Yahya Chusna Arif (Merdeka Malang University, 2021)
To save energy nowadays is recommended to switch to renewable energy sources. In Indonesia, solar energy is abundant, so PLTS is made. The supply of PLTS is expected to reach maximum use. However, solar panels have many obstacles such as variations in temperature and sunlight intensity, MPPT systems are needed to find the maximum power point of the solar panels. Unfortunately, in Indonesia, the sunlight of short duration with the ideal irradiation time that can produce electricity from solar panels is 4 to 5 hours per day, so a PLN supply is still needed to support the continuity of the power supply. Because two sources are used, there is a problem where the load needs high continuity during power switching, so STS (Static Transfer Switch) is used for very fast power switching. Simulation results, when using EMR (Electromechanical Relay) the power transfer process takes 50ms or 5 cycles while STS takes 2ms or ¼ cycles. With very fast response to STS, sensitive equipment is kept safe from power quality disturbances such as voltage sag and voltage swell.